1995
DOI: 10.1364/ao.34.000169
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Langmuir–Blodgett films investigated by a photoacoustic technique

Abstract: A photoacoustic (PA) technique based on a four-layer prism configuration has been developed for nondestructive determination of the optical properties of Langmuir-Blodgett (LB) films, in which the PA signal amplitudes are measured as functions of the incident angle of light. With this technique the experimental PA angular spectra of manganese stearate and cadmium stearate LB films were obtained. Based on the electromagnetic theory and taking into account the anisotropic properties of LB films, as well as use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It should be noted that a similar, but more computationally and physically complicated non-thermally confined photoacoustic refractometry technique was accomplished in the early 1990s. In that case, researchers relied upon the analysis of resonant optical modes in Langmuir-Blodgett films [44][45][46][47] and were able to produce refractive index estimates on the order of 0.01. In traditional reflectometry, light is measured after its interaction with a sample in two linear polarization states to determine refractive index.…”
Section: Pas/tirpas Refractometrymentioning
confidence: 99%
“…It should be noted that a similar, but more computationally and physically complicated non-thermally confined photoacoustic refractometry technique was accomplished in the early 1990s. In that case, researchers relied upon the analysis of resonant optical modes in Langmuir-Blodgett films [44][45][46][47] and were able to produce refractive index estimates on the order of 0.01. In traditional reflectometry, light is measured after its interaction with a sample in two linear polarization states to determine refractive index.…”
Section: Pas/tirpas Refractometrymentioning
confidence: 99%
“…Beyond the mathematical description, applications of the photoacoustic effect 54 span many imaging modalities such as microscopy, tomography, and even molecular imaging owing to the photoacoustic effect having high sensitivity due to the large optical absorption due to the naturally present chromophore hemoglobin. Other applications of the photoacoustic effect even include the estimation of various thin film properties 15,16,20,21,24,[26][27][28][29][30][31][32][36][37][38][39]41,42,56,83,84 . However, PAS does have certain limitations: (1) its extensive optical penetration depth eliminates the ability to probe near-field optical properties at surfaces (2) its efficiency of capturing the emitted acoustic energy is low due to spherical propagation of the majority of the energy away from the detector (3) samples must include chromophores in the wavelength regime under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, previous investigations have shown that increased sensitivity and utility are possible with modern polyvinylidene fluoride (PVDF) ultrasonic detectors and q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG) lasers. Specifically, nanosecond-pulsed Nd:YAG lasers result in a 10 6 fold increase in the peak power, which enables EFPA techniques to become useful tools for evaluating the optical properties of a variety of materials and interfaces 5,6,15,18,[21][22][23][24][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]84,96 . Additionally, previous work has further shown the capability of such techniques to determine structural information about materials at an interface, which was previously never achievable with traditional photoacoustic spectroscopy (PAS) technologies due to their relatively large penetration depth 53,55,57,59,61,62,69,73,75,80,81 .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the mathematical description, applications of the photoacoustic effect 54 span many imaging modalities such as microscopy, tomography, and even molecular imaging owing to the photoacoustic effect having high sensitivity due to the large optical absorption due to the naturally present chromophore hemoglobin. Other applications of the photoacoustic effect even include the estimation of various thin film properties 15,16,20,21,24,[26][27][28][29][30][31][32][36][37][38][39]41,42,56,83,84 . However, PAS does have certain limitations: (1) its extensive optical penetration depth eliminates the ability to probe near-field optical properties at surfaces (2) its efficiency of capturing the emitted acoustic energy is low due to spherical propagation of the majority of the energy away from the detector (3) samples must include chromophores in the wavelength regime under consideration.…”
Section: Introductionmentioning
confidence: 99%